Application of colloid surface-active substances as a nanocatalyst of reactions cement hydration - Shishkin, Alexander; Shyshkina, Alexandra (European Journal of Applied Sciences, 2021)
The purpose of this work is to establish the fundamental possibility of using complex complexes consisting of colloidal and molecular surfactants to catalyze the hydration of cement compositions, the study of mechanical properties. As a result of research, it was found that the introduction of colloidal surfactant into the reaction powder concrete leads to a sharp increase in the strength of concrete at the age of 7 days. It is noted the presence of the optimal content of colloidal surfactant in the amount of 0.0007% by weight of water, which ensures the formation of the maximum strength of the system. In the next step of the experiment, an additional molecular surfactant was introduced into the system. As a result of experiments it was found that the introduction of this substance increases the strength of concrete. Thus, it was found that dimers of colloidal surfactant, which are nanocatalysts for cement hydration reactions, lead to an increase in the strength of concrete and the rate of its formation